Nonlinear analysis of monolithic beam-column connections for reinforced concrete frames - Alva,Gerson (2020)
abstract: This paper deals with nonlinear analysis of deformability of monolithic beam-column connections for bending moments in framed reinforced concrete structures. Due to the simplicity, the connections deformability is considered by using an analytical model of moment-rotation curve. Material nonlinearity of the structural elements is considered by using the flexural stiffness obtained in moment-curvature relationship of the sections. The formulation of the analytical model to obtain the relative rotations between beam and column and the formulation to construct moment-curvature curves is deduced and presented to allow the computational implementation in structural analysis software. The numerical simulations carried out in this study indicated that even in the case of monolithic connections, taking into account the bending moment deformability of the connections leads to significantly better results than the hypothesis of fully rigid connections.